The Income Volatility of U.S. Commercial Farm Households. (19th April 2018) - Key, Nigel; Prager, Daniel L; Burns, Christopher B
Abstract: This study uses a newly created panel dataset drawn from the 1997 to 2013 Agricultural Resource Management Survey to provide the first national estimates of income volatility for commercial farm households in the United States. Results show that the income of commercial farm households is substantially more volatile than that of all U.S. households—though the volatility of farm income is not more volatile than income from nonfarm self‐employment. Using a regression analysis, we identify operator, operation, and regional characteristics associated with higher income volatility, providing information that could improve targeting of risk‐mitigating programs. We find that farm income volatility has declined for farms specializing in program crops in recent decades, supporting the hypothesis that the expansion of the federal crop insurance program helped reduce farm income risk.